Pertanggungjawaban Notaris Terhadap Akta Autentik Yang Berindikasi Tindak Pidana Dalam Upaya Mewujudkan Perlindungan Hukum Kepada Masyarakat - Yuliana Yuliana; Ismail Ismail; Puguh Aji Hari Setiawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research examines the liability of notaries for authentic deeds under the UUJN. While the UUJN does not specifically regulate criminal sanctions for notaries, the Criminal Code can be applied. Violations by notaries can lead to lawsuits against the Ministry of Law and Human Rights. The UUJN regulates the guidance and supervision of notaries by the Notary Supervisory Council and MKN. The primary focus of this research is the final decision of the Regional Notary Supervisory Council regarding administrative sanctions as outlined in Article 73 of the UUJN. The research methodology employed is a normative juridical legal research approach. The legal materials utilized in this research include primary legal materials, secondary legal materials, and tertiary legal materials. The results of the research indicate that the legal protection efforts of the community, particularly those who feel harmed by notaries in the context of notarial acts that indicate criminal acts, are carried out through a form of reactive protection, namely the filing of complaints with the Notary Supervisory Panel. The evidence presented to the Regional Notary Supervisory Panel, the district courts in civil cases for compensation and law enforcement officials (Police) in criminal cases, demonstrates the existence of evidence that can be used to support claims of criminal acts by Notaries. However, the Decision of the Regional Notary Supervisory Panel only imposes Administrative Decisions on Notaries who indicate criminal acts with verbal or written warnings.